2019
DOI: 10.7150/ijbs.35128
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 in Endometriosis

Abstract: Endometriosis (EMS) is the most common gynecological disease in women of reproductive age, and it is associated with chronic pelvic pain, dyspareunia and infertility. As a consequence of genetic, immune and environmental factors, endometriotic lesions have high cyclooxygenase (COX)-2 and COX-2-derived prostaglandin E 2 (PGE 2) biosynthesis compared with the normal endometrium. The transcription of the PTGS2 gene for COX-2 is associated with multiple intracellular signals, which converge to cause the activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 184 publications
0
68
0
1
Order By: Relevance
“…COX2 and PGE2 are related to the pathogenesis of endometriosis. A high level of COX-2 due to various factors such as estrogens, hypoxia and environmental pollutants could suppress apoptosis and increase cell proliferation through PGE2 and its receptors EP2, and EP4 in endometriosis (143). In addition, experimental studies with intralesional injections of ASA, in rabbits with peritoneal endometriosis, eliminate endometriotic lesions (144).…”
Section: Lipoxinsmentioning
confidence: 99%
“…COX2 and PGE2 are related to the pathogenesis of endometriosis. A high level of COX-2 due to various factors such as estrogens, hypoxia and environmental pollutants could suppress apoptosis and increase cell proliferation through PGE2 and its receptors EP2, and EP4 in endometriosis (143). In addition, experimental studies with intralesional injections of ASA, in rabbits with peritoneal endometriosis, eliminate endometriotic lesions (144).…”
Section: Lipoxinsmentioning
confidence: 99%
“…Among the inflammatory mediators stimulated, IL-8 [a neutrophil chemotactic factor, also called C-X-C motif chemokine ligand 8 (CXCL8)], monocyte chemoattractant protein-1 [MCP-1, also called C-C motif chemokine ligand 2 (CCL2)] and cyclooxygenase-2 [COX-2, the inducible enzyme responsible for synthesis of prostaglandins (PGs)], are well-studied 17 . COX-2 upregulation mediated by nuclear factor kappa-B (NF-κB) leads to increased levels of PGs.…”
Section: Classical Viewpointmentioning
confidence: 99%
“…Deep analysis of inflammation in rabbit kidney induced by ligation of the urethra shows that 45 that the contaminated organ surprisingly developed a massive ability to generate prostaglandins because of de novo synthesis of the fresh enzyme, but there was no proposal shown that the new enzyme was a different form 46,47 . In the next few years, the occurrence of two discrete forms of COX in brain tissue was established, which shows different sensitivities to indomethacin 48 .…”
Section: The Development Of Field and Discovery Of Cox-2mentioning
confidence: 99%